Application of the Hartmann–Tran profile to precise experimental data sets of 12C2H2. (November 2015) - Forthomme, D.; Cich, M.J.; Twagirayezu, S.; Hall, G.E.; Sears, T.J.
Abstract: Self- and nitrogen-broadened line shape data for the P e (11) line of the ν 1 + ν 3 band of acetylene, recorded using a frequency comb-stabilized laser spectrometer, have been analyzed using the Hartmann–Tran profile (HTP) line shape model in a multispectrum fitting. In total, the data included measurements recorded at temperatures between 125 K and 296 K and at pressures between 4 and 760 Torr. New, sub-Doppler, frequency comb-referenced measurements of the positions of multiple underlying hot band lines have also been made. These underlying lines significantly affect the P e (11) line profile at temperatures above 240 K and poorly known frequencies previously introduced errors into the line shape analyses. The behavior of the HTP model was compared to the quadratic speed dependent Voigt profile (QSDVP) expressed in the frequency and time domains. A parameter uncertainty analysis was carried out using a Monte Carlo method based on the estimated pressure, transmittance and frequency measurement errors. From the analyses, the P e (11) line strength was estimated to be 1.2014(50) × 10 − 20 in cm molecule − 1 units at 296 K with the standard deviation in parenthesis. For analyzing these data, we found that a reduced form of the HTP, equivalent to the QSDVP, was most appropriate because the additional parameters included in the full HTP were not well determined. As a supplement to this work, expressions for analytic derivatives and a lineshape fitting code written in Matlab for the HTP are available. Abstract : Highlights: Accurate line shape measurements for P(11) of ν 1 + ν 3 band of acetylene. Comparison of line shape models. Multispectrum fitting of experimental data to Hartmann–Tran profile. Calculation of algebraic derivatives for Hartmann–Tran profile with respect to experimental parameters. Sample Matlab code for Hartmann–Tran profile data fitting.